Comprehensive analysis of the mitochondrial genome of Iris domestica emphasizing multichromosomal organization and repeat-mediated homologous recombination - Ouyang, Lizhi; Li, Xinyu; Wang, Ruili; Chen, Yixuan; Wang, Shuo; Wang, Jianfang; Tian, Yelin (Frontiers in Plant Science, 2025)
Background: Iris domestica is a perennial herb valued for both its ornamental and medicinal properties. Despite its significance, no comprehensive analysis of its mitochondrial genome has been previously reported. Plant mitochondrial genomes are known for their large size, structural complexity, and frequent recombination events. This study aims to provide the first complete assembly and characterization of the mitochondrial genome of I. domestica, with a focus on its structure, gene content, repeat elements, and RNA editing sites.We used GetOrganelle and Unicycler software to hybrid assemble Nanopore and Illumina data to obtain the mitochondrial genome of I. domestica. The mitochondrial genome of I. domestica consists of four contigs: contig1 (222,498 bp), contig2 (90,780 bp), contig3 (42,563 bp), and contig4 (39,247 bp). Two repeat sequences, R1 (7,784 bp) and R2 (3,519 bp), facilitate the conformation of three circular chromosomes, suggesting a complex multi-chromosomal structure. A total of 34 protein-coding genes, including 24 core genes and 10 non-core genes were identified. Analysis of tandem repeat elements revealed significant variability, with Chromosome 1 showing the highest diversity of SSRs and scattered repeats. Additionally, 20 homologous fragments were identified between the mitochondrial and chloroplast genomes, accounting for 1.10% of the mitochondrial genome.Phylogenetic analysis based on 24 conserved mitochondrial genes placed I. domestica in close relation to Iris domestica and Crocus sativus. Furthermore, 545 RNA editing sites were identified, with notable variations across genes, suggesting that RNA editing plays a significant role in regulating mitochondrial gene expression.The complete assembly of the I. domestica mitochondrial genome reveals a complex multichromosomal structure characterized by recombination events. The high number of RNA editing sites and the presence of transferred plastid DNA highlight the dynamic nature of the genome, contributing to its adaptability and evolution. These findings provide a genetic foundation into the plant's medicinal properties, adaptive mechanisms, and potential for environmental resilience.